2021
DOI: 10.3389/fvets.2021.724491
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effective Material Basis and Mechanism of Traditional Chinese Medicine Prescription (QJC) Against Stress Diarrhea in Mice

Abstract: Stress diarrhea is a major challenge for weaned piglets and restricts pig production efficiency and incurs massive economic losses. A traditional Chinese medicine prescription (QJC) composed of Astragalus propinquus Schischkin (HQ), Zingiber officinale Roscoe (SJ), and Plantago asiatica L. (CQC) has been developed by our laboratory and shows marked anti-stress diarrhea effect. However, the active compounds, potential targets, and mechanism of this effect remain unclear and warrant further investigation. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Luteolin protected against intestinal inflammation both in cellular models and in mice ( 13 , 14 ). Luteolin had particularly powerful effects in alleviating diarrhea by mitigating the pathological condition of small intestine tissue and maintaining electrolyte balance ( 15 , 16 ). Furthermore, luteolin was reported to suppress NO production ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin protected against intestinal inflammation both in cellular models and in mice ( 13 , 14 ). Luteolin had particularly powerful effects in alleviating diarrhea by mitigating the pathological condition of small intestine tissue and maintaining electrolyte balance ( 15 , 16 ). Furthermore, luteolin was reported to suppress NO production ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its exceptional anti-inflammatory, anti-apoptotic, and antioxidant qualities, Scu can potentially shield cells from a range of stimuli, such as high glucose (Li et al, 2020), amyloid β (Huang, Xu, et al, 2019), and LPS (Fu, Shao, et al, 2019). In addition, previous studies have demonstrated that Scu exerted its protective effect by inhibiting the PI3K/Akt signaling pathway (Ha et al, 2021;Zhang et al, 2021). Thus, Scu has the potential to decrease OA progression by inhibiting inflammation via the PI3K/Akt/ NF-κB signaling pathway.…”
mentioning
confidence: 99%